Identifikasi Tanaman Penghasil Resin dan Polen di Pondok Pesantren Nurul Islam Sekarbela Kota Mataram - Primawati, Sri Nopita; Jannah, Husnul (Biocaster : Jurnal Kajian Biologi, 2022)
Indonesia is a tropical country that has abundant natural wealth in the form of flora and fauna. One of the fauna that is beneficial to humans is the honey bee. An influential factor in the success of honey bee cultivation is the availability of bee feed in the form of flowering plants. The flowers of these plants contain nectar, pollen, or nectar and pollen which is very influential in honey production. The availability of a 500 m wide yard at the Nurul Islam Sekarbela Islamic Boarding School, Mataram City, is currently only used as a living pharmacy planted with medicinal plants and ornamental plants, such as several types of flowers and there are several large trees such as mango trees as shade trees. Almost all types of flowering plants are a source of bee food, because flowers are pollen producers. This study uses an exploratory method with purposive sampling technique. After determining the sampling point, then the process of identifying what plants were found in the Nurul Islam Islamic Boarding School Area was carried out. This identification uses the key to the determination of resin and pollen-producing plants, and is based on related scientific journals. The results of the research that have been carried out obtained 16 types of resin-producing plants, namely: four o'clock flowers, red shoots, sunflowers, turi, purslane, palm, kastuba, miana, longan, mango, rambutan, lime, banana, guava, avocado, and jackfruit. So it can be concluded that the grounds of the Nurul Islam Islamic Boarding School can be used as a beekeeping by placing bee stubs in tall trees, away from disturbances from students or the surrounding community.